Platelet parameters in children with chromosome 22q11 deletion and conotruncal heart defects. (5th March 2018) - Anilkumar, Alka; Vasudevan, D. M.; Kappanayil, Mahesh; Sundaram, K. R.; Krishna Kumar, R.; Nampoothiri, Sheela
Abstract: Background and Objectives: The 22q11 deletion syndrome is associated with a wide spectrum of phenotypic features, hence clinical diagnosis is difficult. Individuals with this syndrome are found to have a risk of developing transfusion associated graft‐versus‐host reaction, if they are given nonirradiated blood. Our aim was to elucidate whether chromosome 22q11 deletion in children with syndromic conotruncal heart defects is associated with platelet abnormality. Materials and Methods: The genetic analysis was performed by standard cytogenetic and Fluorescence in situ hybridization technique. The platelet parameters in 39 patients with chromosome 22q11 deletion were compared with 154 cases without deletion. Results: In deletion versus no deletion group, the mean of mean platelet volume (MPV) was 10.5 ± 2.5 vs 7.6 ± 1.5 fL, platelet count was 225 ± 80.7 and 339 ± 127.3 × 10 9 /L and frequency of high MPV was 49% vs 7% ( P < .0001). The MPV was associated with a sensitivity of 90.9% and a specificity of 79.6% at a cutoff value of 8.32 fL, (area under the ROC curve 91%). A nonsignificant negative correlation was found between MPV and platelet count ( r = −0.152; P = .361) in children with deletion. Conclusion: A cutoff value of 8.32 fL for MPV can be an indicator of high risk of chromosome 22q11 deletion in individuals with syndromic conotruncal defects. Individuals with chromosome 22q11 deletion should be given irradiated blood especially during cardiac surgery. Further investigation should clarify the etiology behind variation in frequency of high MPV in different conotruncal lesions.